(3GdJHjGf aj GdHjGf GdJHjGf aj GdeYGfi hGdHjGfs - (3GdMSjf Hf eMeO Hf YHO Gddg, TQa GdOjf GdpqWjHj,J (B743 (3g` s ((3eOjfI jRO s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQbJ HSjfGA eMGeOg ai SeGA GdeYGfi ef TehS GdHjGf CeG HYO aEfi Chdi eG GYedJ ajg GdbQGFM hYdbJ Hg GdCacGQ GddhGbM s
(3BNQgG (B:s
(3hbGd TYQ gPG GdPi GNJUQ GdeYfi GdHdjZ dg hCUHMJ WhYg LhGeY Gdcde gPG gh GdefPQ GdCei CaUM ef HGdVGO ef Ydjg UdhGJ Gddg hSdGeg Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HChdgG agQSs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdHdGZIs